Genetic, molecular and developmental analysis of the glutamine synthetase isozymes of Drosophila melanogaster. - Caggese, C.; Barsanti, P.; Viggiano, L.; Bozzetti, M.P.; Caizzi, R. (Genetica, 1994)
The glutamine synthetase isozymes of Drosophila melanogaster offer an attractive model for the study of the molecular genetics and evolution of a small gene family encoding enzymatic isoforms that evolved to assume a variety of specific and sometimes essential biological functions. In Drosophila melanogaster two GS isozymes have been described which exhibit different cellular localisation and are coded by a two-member gene family. The mitochondrial GS structural gene resides at the 21B region of the second chromosome, the structural gene for the cytosolic isoform at the 10B region of the X chromosome. cDNA clones corresponding to the two genes have been isolated and sequenced. Evolutionary analysis data are in accord with the hypothesis that the two Drosophila glutamine synthetase genes are derived from a duplication event that occurred near the time of divergence between Insecta and Vertebrata. Both isoforms catalyse all reactions catalysed by other glutamine synthetases, but the different kinetic parameters and the different cellular compartmentalisation suggest strong functional specialisation. In fact, mutations of the mitochondrial GS gene produce embryo-lethal female sterility, defining a function of the gene product essential for the early stages of embryonic development. Preliminary results show strikingly distinct spatial and temporal patterns of expression of the two isoforms at later stages of development.